2006
DOI: 10.1890/0012-9658(2006)87[1744:dfbcga]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Demographic Feedback Between Clonal Growth and Fragmentation in an Invasive Seaweed

Abstract: Many abundant plants, invertebrates, and seaweed are clonal, and this allows the formation of high-density aggregations, foraging, and the placement of modules into new space, and rapid rates of expansion. For these species, population density and rates of expansion are functions of recruitment of asexual modules and post-recruitment vegetative growth and survivorship. In this study, we provide the first experimental test of the relative importance of these two processes in determining the abundance of a clona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 65 publications
(136 reference statements)
0
37
0
Order By: Relevance
“…The capacity for vegetative propagation is fundamental to the success of some NIS (Nyberg & Wallentinus, 2005;Wright & Davis, 2006), leading to higher rates of successful colonization (Norton & Mathieson, 1983). Gracilaria vermiculophylla was always abundant and reproductive even though mature male gametophytes were never observed during the sampling period.…”
Section: Field Studiesmentioning
confidence: 99%
“…The capacity for vegetative propagation is fundamental to the success of some NIS (Nyberg & Wallentinus, 2005;Wright & Davis, 2006), leading to higher rates of successful colonization (Norton & Mathieson, 1983). Gracilaria vermiculophylla was always abundant and reproductive even though mature male gametophytes were never observed during the sampling period.…”
Section: Field Studiesmentioning
confidence: 99%
“…The capacity to reproduce asexually has been often cited as a characteristic conducive to invasion success (Sakai et al 2001), though the correlation has been reported most thoroughly in plant systems (Ruesink & Collado-Vides 2006, Wright & Davis 2006, Burns 2008, Milbau & Stout 2008. Only a few studies have explored the role of asexual reproduction in the successful invasions of invertebrate taxa (Ting & Geller 2000, Facon et al 2003, Stadler et al 2005, and none have directly tested the hypothesis that asexuality contributes to invasiveness.…”
Section: Asexual Reproduction and Colonization Success Of Nematostellmentioning
confidence: 99%
“…Glynn, personal communication). Blooms were concentrated on the fore-reef slope adjacent to established oV-reef patches of Caulerpa, suggesting that the alga moved from the oV-reef reservoirs by vegetative growth of established thalli and fragmentation, both of which are known to be eVective mechanisms of population spread within the genus Caulerpa (Smith and Walters 1999;Wright and Davis 2006). Blooming Caulerpa overgrew coral and caused nearly 100% mortality of prostrate, nodular coral species (Psammocora spp.…”
Section: Introductionmentioning
confidence: 99%